The new uses of the enamel matrix derivative: literature review (Research, Society and Development, 2022)
Seeking to demonstrate the recent uses of the enamel matrix derivative (EMD), the objective of this work is to develop a literature review of the use of biomaterial in soft tissues and in the treatment of peri-implantitis. The search for scientific articles was carried out at Pubmed, the selected literature was from 2010 to 2020, found with the following descriptors: “Emdogain And Soft Tissue” and “Emdogain And Peri-Implantitis”. Studies on bone regeneration treatment, bone graft, treatment of patients with systemic disease were excluded. The selected sample consisted of 17 articles, and the results found favor the use of EMD. In the healing of soft tissues around teeth and implants, the works report the good hypotheses in relation to cicatricial cellular events (angiogenesis, fibroplasia and reduction of inflammatory markers) and histological evaluations that EMD promotes when facing surgical wounds. In root coverage of different types of recessions, improvements were also seen with the use of EMD, but procedures based on connective tissue grafts still show superior results. In the treatment of peri-implantitis, EMD seems to present a good result as an adjuvant, but more studies need to be performed. The use of EMD is justified by the possibility of achieving periodontal regeneration in the treated sites and by its positive attributes in the healing process of various periodontal procedures in soft tissues, in the techniques of root covering and in the treatment of peri-implantitis.